2014
DOI: 10.1073/pnas.1415098111
|View full text |Cite
|
Sign up to set email alerts
|

H19 long noncoding RNA controls the mRNA decay promoting function of KSRP

Abstract: Long noncoding RNAs (lncRNAs) interact with protein factors to regulate different layers of gene expression transcriptionally or posttranscriptionally. Here we report on the functional consequences of the unanticipated interaction of the RNA binding protein K homology-type splicing regulatory protein (KSRP) with the H19 lncRNA (H19). KSRP directly binds to H19 in the cytoplasm of undifferentiated multipotent mesenchymal C2C12 cells, and this interaction favors KSRP-mediated destabilization of labile transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 48 publications
(89 reference statements)
5
90
0
Order By: Relevance
“…LncRNA regulates numerous physiological and pathological processes, including cell proliferation [27]. LncRNA H19 is mainly proved to regulate cell activation [28]. In our study, for the first time, H19 regulation of DUSP5 expression was examined.…”
Section: Discussionmentioning
confidence: 85%
“…LncRNA regulates numerous physiological and pathological processes, including cell proliferation [27]. LncRNA H19 is mainly proved to regulate cell activation [28]. In our study, for the first time, H19 regulation of DUSP5 expression was examined.…”
Section: Discussionmentioning
confidence: 85%
“…The information emerging on lncRNA-RBP complexes (lncRNPs), systematically cataloged by Li et al (2015), suggests that the same RBPs can bind coding RNA and ncRNA and affect their post-transcriptional fate in various ways. Indeed, there are increasing examples of RBPs that bind both mRNAs and lncRNAs; for example, HNRNPK binds Oct1 mRNA and lncRNA XIST (Iwasaki et al 2008;Chu et al 2015), AUF1 binds DICER1 mRNA and lncRNA NEAT1 Yoon et al 2014), and KSRP binds NPM mRNA and lncRNA H19 (Cammas et al 2014;Giovarelli et al 2014). …”
Section: Mrna Rnp (Mrnp) and Lncrna Rnp (Lncrnp) Complexesmentioning
confidence: 99%
“…Although heritable changes in gene regulation that occur via modification of the DNA without changes to the DNA sequence are often referred to as epigenetic programming, noncoding RNA (ncRNA)-mediated transcriptional or posttranscriptional regulation is one of the major regulation mechanisms for epigenetic programming (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Recent studies have identified thousands of long ncRNAs (lncRNAs) (17,23) in mammalian genomes that regulate gene expression in a variety of immunological processes (31)(32)(33)(34)(35), such as differentiation of T cells (33,36) and dendritic cells (DCs) (35).…”
Section: T Uberculosis (Tb) Caused By Mycobacterium Tuberculosis (Mtb)mentioning
confidence: 99%